PHYTOCHEMICAL SCREENING, TOTAL ANTIOXIDANT ACTIVITY AND TOXICITY TEST ON METHANOL EXTRACT OF ANDROGRAPHIS PANICULATA LEAF - Thalia Gabriella Siriwa; Frans Ferdinal (Universitas Pahlawan Tuanku Tambusai, 2023)
Antioxidants are compounds that can inhibit the oxidation of a molecule and neutralize radicals that have a negative impact on cells. In addition, antioxidants can also inhibit the activity of reactive oxygen species (ROS) by regulating the superoxide dismutase enzyme. When the level of ROS is greater than that of antioxidants, an imbalance state called oxidative stress can occur. In this case, antioxidants play an important role in preventing ROS activity. Sambiloto or,